(untitled) (Prosiding Seminar Nasional Masyarakat Tangguh, 2024)
Banjar Regency is one of the districts affected by the most severe floods in 2020 and 2021, it is known that the prevalence of skin diseases in people affected by floods is 47.57%. Previously the Covid-19 pandemic that occurred had limited community activities, plus stagnant floods added to the impact felt by the community, the most widely felt was the impact on health and the economy. Kalangkala is a typical Kalimantan plant which has many benefits, it is known that it contains flavonoid compounds and is proven to inhibit the growth of bacteria that cause skin diseases. It is hoped that education related to the kalangkala plant will be able to increase public knowledge regarding nutritious plants that are around that are able to overcome athlete’s foot so that they are able to carry out self-medication. Education was carried out through audiovisual media used in this activity with 29 participants participating in this activity. First, a pre-test was carried out to measure community knowledge before being given educational material, then a post-test was carried out after being given educational material to see community understanding. From this activity, the result was that the community had previously known and consumed the kalangkala plant but did not know that the kalangkala plant had properties and could overcome athlete’s foot. This community service activity showed an increase in the participants’ knowledge regarding the use of the kalangkala plant in treating athlete’s foot, it can be seen from the percentage results which showed an increase in public understanding regarding the kalangkala plant having efficacy of as much as 60% and 44% of kalangkala being able to overcome athlete’s foot. It is hoped that this education will not only increase public awareness and knowledge of the kalangkala plant for treating athlete’s foot, it can also help improve the health status and economy of the community.